Analisis Implementasi Etika Bisnis Pada Era Digitalisasi - Adyanto Armando Purba; Wanda Nilam Sari Br. Harefa; Muhammad Bagas Ardhana; Bonaraja Purba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is as a basis for finding out how the application of business ethics occurs in the current era of digitalization. The discussion focuses on looking at how business can develop in the era of globalization and digitalization while maintaining the basic/rules of doing business. So, based on the results and discussion of this research, it can be concluded that the rules in doing business still exist, business conducted online also still has ethics as a basis for regulating business people in running their business.